2005
DOI: 10.1590/s1413-86702005000500006
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Streptococcus pneumoniae to penicillin in the state of Minas Gerais, Brazil from 1997-2004

Abstract: We monitored the susceptibility to penicillin of invasive strains of Streptococcus pneumoniae in two reference laboratories; 502 positive cultures from patients with an active invasive infectious process were analyzed. Streptococcus pneumoniae was identified through conventional procedures, and the oxacillin disc diffusion method was used to check for penicillin susceptibility. Statistical analysis included calculations of the frequency distribution, with 95% confidence intervals (CI), as well as chi-square te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…20 Data from Brazil are still scarce and fragmented. Some studies have shown low 21,22 or no 23 rates of non-susceptibility to penicillin, whereas others have indicated rates around 20%; 24-25 serotypes 14, 23F, 6B, and 19F have been most commonly associated with this resistance in brazilian studies. 24,25 Full resistance (MIC >4.0 mg/ml) to penicillin was not found among the isolates included in this study.…”
Section: Discussionmentioning
confidence: 98%
“…20 Data from Brazil are still scarce and fragmented. Some studies have shown low 21,22 or no 23 rates of non-susceptibility to penicillin, whereas others have indicated rates around 20%; 24-25 serotypes 14, 23F, 6B, and 19F have been most commonly associated with this resistance in brazilian studies. 24,25 Full resistance (MIC >4.0 mg/ml) to penicillin was not found among the isolates included in this study.…”
Section: Discussionmentioning
confidence: 98%
“…17 When this study was enlarged, including samples collected up to 1999 from children up to 6 years old, the total resistance rate was 20.7%, 13 a rate similar to the 20% value found in other local studies carried out in Brazil. 25,26 In the state of Minas Gerais, local studies have revealed rates of 11.8% of oxacillin-resistant strains 27 and 15.5% of penicillin-resistant pneumococcal invasive strains according to the traditional criteria. 28 According to the traditional criteria, the classification as resistant is clinically important in cases of acute otitis media and meningitis, but it is not relevant in cases of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the microbiological patterns at the local and regional levels or about the patterns of CAP severity in adults in Brazil. (5,6) Treatment protocols and case management protocols are often based on investigations of the disease in countries in the northern hemisphere. It should be borne in mind that the worldwide multicenter antimicrobial surveillance program, known as SENTRY, and the Latin American Sistema Regional de Vacunas (Regional Vaccination System) II program have been a reference for guiding therapy in Brazil.…”
Section: Introductionmentioning
confidence: 99%